PPP-Based Transport Infrastructure Development in Eastern Indonesia: A Case Study of Makassar–Parepare Railway - Fathurrahman; Vivian Alvianti (Journal of Infrastructure Policy and Management, 2026)
The Makassar–Parepare railway project is Indonesia’s first Public-Private Partnership (PPP) initiative in the railway sector, with an investment value of IDR 1.1 trillion and operational costs of IDR 1.9 trillion. This study examines the relevance of Kingdon’s Multiple Streams Framework in public administration, particularly in the implementation of large-scale transport infrastructure. Using a qualitative-interpretative case study based on literature synthesis, the research shows that Kingdon’s framework is still relevant in explaining how policy decisions are shaped by contextual dynamics, actor interactions, and political opportunities. The findings highlight the important role of key actors in selecting governance models, as reflected in the partnership between the Ministry of Transportation and PT Celebes Railway Indonesia. This case demonstrates that governance choices influence agenda-setting and project implementation in infrastructure megaprojects. Overall, the study reveals that policy implementation is driven not only by the substance of policy problems but also by institutional interests, power relations, and strategic interactions among different actors.